Supporting verbs dar/levar: a case of grammaticalization? - Smarsaro, Aucione (2015)
This paper focuses on the use of the support verbs “dar” (give) and “levar” (take/get) followed by predicational nouns, occurring in sentences structured as N0 dar Npred a N1 = N1 levar Npred de N0 (João deu um fora em Ana = Ana levou um fora de João), in contexts in which there is a syntactic-semantic correspondence. We also aim to evaluate the extent to which the facts confirm the hypothesis that, in this type of structure, these support verbs constitute a grammatical word. The description includes a set of examples widely used in the web and yielded by relying on native speakers´ intuition about acceptability. Lexicon-Grammar (GROSS, 1975) and Grammaticalization (HEINE; Claudi; Hunne meyer , 1991) are articulated in order to confirm whether the transformation of the plain verb dar/levar into a support verb can be considered a process of grammaticalization.